Impact of Rapid Application Development (RAD) Methodology on Web-Based Production Report Information System Development: A Case Study at PT. Nichias Metalwork Indonesia - Maulana, Donny; Amali, Amali (DPPM Universitas Pelita Bangsa, 2023)
In general, production management involves a variety of jobs where specialists in management can express their judgment. Due to ongoing Due to ongoing company challenges, challenges, the production section's data input procedure still utilizes paper forms that are physically filled out and then collected at the PT. Nichias Metalwork Indonesia. Because they have to take the report form on the supervisor's desk, it is more difficult for the admin to enter data. Rapid Application Development (RAD) is the name of the research methodology that was employed. This approach emphasizes realizing the era of quick software development where the model is created early to define user needs. The mechanism for producing reports was developed. The objective of this study is to develop and build a production report information system to streamline the process of entering and reporting production at PT. Nichias Metalwork Indonesia to in there to reduce the disparity between output and inventory.